Effects of land-based wind turbine upsizing on community sound levels and power and energy density. (15th May 2023) - Hoen, Ben; Darlow, Ryan; Haac, Ryan; Rand, Joseph; Kaliski, Ken
Graphical abstract: Highlights: Technological advancement has resulted in larger – and louder – wind turbines. Future wind projects will use fewer turbines per unit of land due to setbacks. But, project capacity and output will likely increase for those units. Average sound levels across future host communities will likely decrease. Economic benefits will likely increase as project capacity and output increases. Abstract: Multiple technological, social, and market factors of wind power are evolving rapidly. Most notably, significant wind turbine scaling is occurring and is forecasted to continue. While the larger turbines expected to be deployed in the future are more powerful and efficient, they are also expected to operate at higher sound levels and require larger setbacks than those installed in the last decade. These sometimes-competing deployment trends and impacts cannot be understood via simple extrapolations of past trends. This study analyzes the effect of these future larger turbines on wind turbine micro-siting, project-level power and energy density, and community noise impacts. Due to their taller heights, larger rotors, and higher sound power levels, future wind turbines will require larger setbacks from homes and greater inter-turbine spacing, resulting in fewer turbines deployed for a given land area. This research finds these changes more than offset the effect of the higher turbine sound emissions, significantly decreasing the average sound levels that wind plant hosting communities experience. Yet, simultaneously, plant layouts using future turbine designs also result in projects with higher installed capacities and annual energy output for a given land area. These increases will likely lead to increased tax benefits and local income in the community. The deployment of fewer turbines on a smaller number of parcels could have implications on siting flexibility and landowner payments.